Tissue flossing on ankle range of motion, jump and sprint performance: A follow-up study - Driller, M.; Mackay, K.; Mills, B.; Tavares, F. (Physical Therapy in Sport, 2017)
Objectives: Previous results from our laboratory suggest that band flossing results in increased ankle range of motion (ROM) and jump performance 5-min following application. However, the time-course of such benefits is yet to be examined. Design: Parallel group design. Setting: University laboratory. Participants: 69 recreational athletes (32 male/37 female). Main outcome measures: Participants performed a weight-bearing lunge test (WBLT), a counter-movement jump (CMJ) and a 15 m sprint test (SPRINT) pre and up to 45-min post application of a floss band to both ankles (FLOSS) or without flossing of the ankle joints (CON). Results: There was a significant intervention × time interaction in favour of FLOSS when compared to CON for the WBLT (p < 0.05). These results were associated with trivial to small effect sizes at all time points. Small, but non-significant (p > 0.05) benefits were seen for FLOSS when compared to CON for CMJ force (mean ± 90%CI: 89 ± 101 N) and 15 m SPRINT times (-0.06 ± 0.04 s) at 45-min post. Conclusion: There is a trend towards a benefit for the use of floss bands applied to the ankle joint to improve ROM, jump and sprint performance in recreational athletes for up to 45-min following their application.